Problems of integrating artificial intelligence technologies into educational programmes for state and municipal employees - A. O. Bidzhiev (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. In the conditions of active implementation of artificial intelligence technologies in public administration and local self-government authorities, the integration of these technologies into the educational programmes of higher education institutions becomes one of the primary tasks for educational institutions that aim to train highly qualified specialists with knowledge, skills and abilities that fully meet modern demands in the labour market.Goal. The article aims to identify the basic problems faced by higher education institutions when introducing artificial intelligence technologies into their educational programmes, as well as to identify the factors under the influence of which these problems are formed.Materials and methods. The research is based on the analysis of the process of integration of artificial intelligence technologies into educational programmes for state and municipal employees to-be, which takes place within the framework of modernisation of these programmes to meet the modern requirements of state and municipal management institutions.Results and discussion. In the course of the work, the problems faced by higher education institutions in updating their educational programmes in terms of their addition of artificial intelligence technologies were identified, the forms of manifestation of these problems were considered and the factors, the impact of which became the basis for the formation of these problems, were identified.Conclusion. According to the results of the conducted research, it can be concluded that in the process of integrating artificial intelligence technologies into educational programmes for state and municipal employees to-be, the education system has faced a number of problems, the basic ones being the shortage of qualified personnel, the lack of modern technical infrastructure and the low level of development of the profile regulatory and legal framework. Each of these problems was formed not without reason, but under the influence of direct and indirect factors, some of which are not clearly negative and therefore require minimizing the impact only on the process of the analyzed integration. At the same time, the relevance of the identified problems is confirmed by the form of their manifestation, which has an impact both in the context of considering the effectiveness of training an individual specialist and in the context of evaluating the educational institution as a whole.